PL approximation of DBPSK in DF-based cooperative FSO network with pointing error - Agarwal, Deepti; Bansal, Ankur; Kumar, Ashwni (Photonic network communications, 2018)
In this paper, we utilize piecewise linear (PL) approximation to analyze the performance of cooperative free space optical (FSO) network employing differentially modulated binary phase shift keying (DBPSK) data with multiple decode-and-forward (DF) relays. The maximum-likelihood (ML) decoding rule at the destination is approximated by PL approximation which considers the possibility of erroneous relaying and performs very similar to the ML decoder with reduced decoding complexity. The atmospheric fading optical links are modeled by Gamma–Gamma distribution subject to both types of detection techniques, i.e., heterodyne detection and intensity modulation/direct detection (IM/DD) with pointing error. We analytically formulate the probability of error for the multiple-DF relay-based FSO network. However, the novel unified expression of average bit error rate (BER) of PL decoder with single relay and single source to destination pair is derived. Further, we also derive the asymptotic approximate BER of DF-FSO network with multiple relays at high signal-to-noise ratio (SNR) of source to relay links considering heterodyne detection with negligible pointing error. In addition, the unified closed-form expressions of outage probability with single and multiple DF relays are derived in terms of Meijer G function. The expression of outage probability is examined at high SNR in order to obtain analytical diversity order. The impact of different power distribution techniques on outage probability is determined by utilizing power distribution parameters. The derived analytical results are validated through simulation.